2021
DOI: 10.3389/fpsyt.2021.674583
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Training for Awareness Resilience and Action Online Compared to Standard Treatment for Adolescents and Young Adults With Depression: Study Protocol and Analysis Plan for a Pragmatic, Multi-Center Randomized Controlled Superiority Trial

Abstract: Depression in adolescents and young adults is an increasing global health concern. Available treatments are not sufficiently effective and relapse rates remain high. The novel group-treatment program “Training for Awareness, Resilience and Action” (TARA) targets specific mechanisms based on neuroscientific findings in adolescent depression. TARA is framed within the National Institute of Mental Health's Research Domain Criteria and has documented feasibility and preliminary efficacy in the treatment of adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…In that sample measurement, invariance was also confirmed for sex and age-group [20]. Since the scale is intended for clinical application [10] and since valid outcome-measures are needed for both ongoing and future clinical trials, including in participants from a wider age-range than previously studied [9], we here present data on the psychometric properties of RADS-2 in a heterogenous clinical sample with affective symptomatology.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In that sample measurement, invariance was also confirmed for sex and age-group [20]. Since the scale is intended for clinical application [10] and since valid outcome-measures are needed for both ongoing and future clinical trials, including in participants from a wider age-range than previously studied [9], we here present data on the psychometric properties of RADS-2 in a heterogenous clinical sample with affective symptomatology.…”
Section: Introductionmentioning
confidence: 73%
“…For example, the Diagnostic and Statistical Manual of Mental disorders, fifth edition (DSM-5) allows for the replacement of depressed mood with irritability as a core diagnostic symptom criterion [6]. At the same time, both pathophysiological and neurodevelopmental similarities are shared between teenagers and adults up to their mid-twenties [7,8], which has warranted research spanning across this critical age-range [9]. In the evaluation of symptom severity and treatment effectiveness for individual patients, as well as more broadly for research with national and international ambitions, measures of depression that are valid across different contexts, age-groups, and languages are clearly needed.…”
Section: Introductionmentioning
confidence: 99%
“…This is followed by training in interoceptive awareness and techniques to develop metacognition, compassion and care for both the patient and others. The final step is value-based behavioral activation ( Ekbäck et al 2021 ). Specific target areas are sustained threats, sleep and arousal, and attention and cognitive control.…”
Section: Intervention or Preventionmentioning
confidence: 99%
“…Subsequent targets are addressed progressively in a way that gives priority to the domains thought to be driving the psychopathology (18). The development process and a detailed description of the content of the different modules of TARA, as well as their relation to targeted constructs of the RDoC have been thoroughly elaborated in our previous publications in Frontiers' journals (18,20,21). For example, the proposed working mechanism of TARA in relation to the first target of sustained threat and amygdala hyper-reactivity includes practices to increase vagal afference.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the neuro-developmental trajectory of the cerebral cortex (26) suggests that adolescents and young adults share similarities that are rarely addressed in clinical trials, and very few studies have been conducted that cover the critical age-range of 15-22. To resolve remaining questions, we have planned and initiated a multicenter randomized controlled trial (RCT) (20), the pilot phase of which is reported here. Apart from an upcoming U.S. study that will use magnetic resonance imaging as primary outcome, the ISRCTN-and Clinicalrtrials.gov registers (as of February 2023) record no comparable recent nor ongoing trials anywhere in the world.…”
Section: Introductionmentioning
confidence: 99%